Model Desain Pembelajaran PPSI Pada Mata Pelajaran Pendidikan Agama Islam - Petir Jihad Gelegar Halibrata; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2023)
The background of this research is to find out the steps of PAI teachers in the PAI learning design model at SD Negeri 22 Ujung Gurun, Padang City and to find out the strengths and weaknesses in the PAI learning design at SD Negeri 22 Ujung Gurun, Padang City. The method used in this research is qualitative method. The data sources are two informants through interviews, consisting of two Islamic religious education teachers at SD Negeri 22 Ujung Gurun, Padang City. The datas collection techniques are observation, interviews, and documentation. All interview results were then analyzed systematically through four steps of analysis activities, namely (data collection, data reduction, presentation and conclusion). Overall the results of the analysis show; (1) Regarding the steps of the PPSI learning design model at SD Negeri 22 Ujung Gurun, Padang City, there are five: (a) formulating learning objectives (b) Developing evaluation tools (c) Determining teaching and learning activities (d) Planning teaching and learning activities programs ( e) Execution. (2) regarding the excesses and defficiencies of the PPSI learning design model. The results of this study can be used as initial data for further research in examining different issues related to this problem and other issues that are relevant to this context.